Underwater undulatory swimming: linking kinematics, wave analysis and flow visualization - Arellano, R.; Jesús J. Ruíz (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Underwater undulatory swimming (UUS) has aroused the interest of researchers since some swimmers, starting from the Moscow Olympic Games (1980), achieved very good results by swimming longer and longer distances underwater, until its limitation to 15m after the start and the turn or the recent possibility of using it in the backstroke finish. These limits, however, are sufficient for some swimmers to show great differences over the rest in these underwater phases (Ruiz-Navarro et al., 2022). It is our objective to explore in a "holistic" way, all the biomechanical components that could explain a good performance in UUS.